2016
DOI: 10.3233/cbm-160594
|View full text |Cite
|
Sign up to set email alerts
|

Serum TK1 is a more reliable marker than CEA and AFP for cancer screening in a study of 56,286 people

Abstract: Abstract. BACKGROUND:The World Health Organization (WHO) has estimated that the number of cancer patients will increase by about 70% during the next 25 years world-wide. To deal with this problem, WHO has suggested a focus on prevention of tumor incidence and health screening for early detection of people with tumors. OBJECTIVE: To investigate the use of thymidine kinase 1 (TK1), CEA and AFP in serum to discover people with malignant tumors through health cancer screening. METHODS: Of a cohort in 486,085 peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…Usually, α-fetoprotein (AFP) has been used as diagnosis biomarker for screening out HCC patients for decades (Zhang et al 2004;Bai et al 2017). However, studies indicate that AFP has poor sensitivity and specificity for HCC (Akeyama et al 1972;Wang et al 2016). Thus, either doctors or researchers kept craving more efficient biomarkers for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, α-fetoprotein (AFP) has been used as diagnosis biomarker for screening out HCC patients for decades (Zhang et al 2004;Bai et al 2017). However, studies indicate that AFP has poor sensitivity and specificity for HCC (Akeyama et al 1972;Wang et al 2016). Thus, either doctors or researchers kept craving more efficient biomarkers for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Thymidine Kinase 1 (TK1) is a cell cycle regulated DNA synthesis enzyme that is up-regulated in malignant tissues during early stages of cancer development [5,6]. Multiple studies have shown that TK1 levels in serum (sTK1) and tissues correlate with cancer progression, patient outcome and recurrence events [7][8][9][10][11][12]. Although TK1 was initially proposed as a cancer biomarker for several blood cancers [13,14], it has also been shown to be a reliable biomarker for a wide variety of solid malignancies [15][16][17][18][19][20].…”
mentioning
confidence: 99%
“…Studies have reported that the expression levels of miR-183 and thymidine kinase (TK) 1 (TK1) in the peripheral blood of malignant carcinoma patients were significantly increased, suggesting their potential as serological markers for cancer diagnosis [9][10][11][12]. In this study, the expression levels of serum miR-183 https://doi.org/10.1515/biol-2017-0029…”
Section: Introductionmentioning
confidence: 73%